Penerapan Pembelajaran Model Contextual Teaching And Learning (CTL) Dengan Media Realita Untuk Meningkatkan Kreativitas dan Hasil Belajar IPA - Indah Safitri; Ririn Andriani Kumala Dewi (Jurnal Pendidikan Dasar Islam, 2023)
Low creativity and student learning outcomes are caused by a lack of media/visual aids and less than optimal learning management carried out by teachers. This research method uses Classroom Action Research (PTK) which consists of four components, namely Planning, Action, Observation and Reflection. Based on the data results, observation results for cycle I were obtained with a percentage of 72% (fairly good), cycle II with a percentage of 81% (good) and cycle III with a percentage of 92% (very good). The research results show that classically from cycle I with a percentage of 70.43% (medium creativity) it increased in cycle II with a percentage of 86.13% (high creativity) and increased very well in cycle III with a percentage of 90.08% (high creativity). Student learning outcomes in cycle I received an average score of 56 and the percentage completed was 43%, increasing in cycle II with an average score of 77 and the percentage completed was 88%, increasing very well in cycle III by 96%. Thus, the application of the CTL model can increase creativity and science learning outcomes regarding human growth and development in class III students at MI Hidayatul Islamiyah for the 2021/2022 academic year